Oxytocin and early parent-infant interactions: A systematic review - Naomi Scatliffe; Sharon Casavant; Dorothy Vittner; Xiaomei Cong (Elsevier, 2019)
Objectives: Social relationships throughout lifespan are critical for health and wellbeing. Oxytocin, often called the 'hormone of attachment' has been suggested as playing an important role in early-life nurturing and resulting social bonding. The objective of this paper is to synthesize the associations between oxytocin levels and interactions between infants and parents that may trigger oxytocin release, and in turn facilitate attachments. Methods: A comprehensive cross-disciplinary systematic search was completed using electronic databases. The inclusion criteria included studies that focused on mother-infant and father-infant interaction and measured both baseline and post-interaction oxytocin levels. Results: Seventeen studies were included in the final systematic review. The reviewed studies used mother-infant and/or father-infant play and skin-to-skin contact between maternal-infant and paternal-infant dyads to examine the oxytocin role in early life bonding and parenting processes. Studies showed a positive correlation between parent-infant contact and oxytocin levels in infancy period. Increased maternal oxytocin levels were significantly related to more affectionate contact behaviors in mothers following mother-infant contact, synchrony, and engagement. Meanwhile, increased paternal oxytocin levels were found to be related to more stimulatory contact behaviors in fathers following father-infant contact. Oxytocin levels significantly increased in infants, mothers and fathers during skin-to-skin contact and parents with higher oxytocin levels exhibited more synchrony and responsiveness in their infant interactions. Conclusion: The review suggests that oxytocin plays an important role in the development of attachment between infants and parents through early contact and interaction. The complexities of oxytocinergic mechanisms are rooted in neurobiological, genetic, and social factors. Keywords: Bonding, Development, Humans, Object attachment, Oxytocin, Parenting, Parent-infant contact, Social behavior